Using the Blues as a Teaching Tool - Howard E. Frisbee (Journal of Applied Communications, 1972)
Off we go into the wild blue wonder! Blue wonder? Yes, that's just how I felt today as I filled in the forms and sealed the envelope for another year's shot at the "blue."